"Moved on"? An exploratory study of the Cashless Debit Card and Indigenous mobility. Issue 1 (27th November 2019) - Vincent, Eve; Markham, Francis; Klein, Elise
Abstract: What is the relationship between the first two trials of the Cashless Debit Card (CDC) and Indigenous mobility? In Ceduna, Vincent conducted ethnographic research into lived experiences of the first CDC trial. In the East Kimberley, Klein conducted 51 structured interviews with people on the card and 37 semi‐structured interviews with key informants. Markham used regression analysis of net migration rates at the Statistical Area 2 level to determine whether the CDC trial sites were associated with greater net population loss in 2016 census data than comparable locations. Our exploratory study finds significant local talk of displacement arising from the introduction of the CDC, as well as discussion of short‐term trips away from the trial sites being made more difficult. The regression analysis found that the net migration rate was 9.3 per cent points (95% CI: 2.0, 16.5) lower in Ceduna, Wyndham and Kununurra when compared with a group of comparable towns, and 5.2 per cent points (95% CI: 0.9, 9.5) lower when compared with Australia as a whole, meaning that the populations of these towns declined faster than those of comparable towns. Policy effects on mobility should be taken seriously by researchers and policymakers when considering place‐based welfare policy.